Manajemen Diri Pada Pasien Diabetes Melitus Tipe 2 Di Puskesmas Dinoyo Malang - Hastutiningtyas, Wahidyanti Rahayu; Rosdiana, Yanti; Ina, Irnawati Nona (Universitas Tribhuwana Tunggadewi, 2024)
Proper self-management is crucial for individuals living with Type 2 Diabetes Mellitus (T2DM). T2DM is a metabolic disorder characterized by high levels of insulin production, decreased insulin activity, or both. The aim of this research was to assess the self-management practices of T2DM patients at the Dinoyo Primary Health Center in Malang. Descriptive analysis was employed as the research method. The study population comprised 44 T2DM patients, of whom 40 were selected as research samples using simple random sampling. Data were collected through a self-completed questionnaire, specifically the Diabetes Self-Management Questionnaire. The findings indicate that the majority of respondents at the Dinoyo Primary Health Center in Malang, namely 30 individuals (75.0%), demonstrated poor self-management practices in managing their T2DM. Future research endeavors should aim to identify additional factors contributing to poor self-management abilities among T2DM patients, such as the level of family support and blood sugar control.